PERSEPSI GURU TENTANG METODE DISKUSI KELOMPOK DALAM MENERAPKAN KETERAMPILAN BERBICARA DI KELAS V MI AL MUAWANAH KAB. TANGERANG - Putri, Abdahamidah; Soleh Hapudin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the fact that the learning process in elementary schools does not solely depend on teaching materials but is also influenced by teachers’ perceptions of classroom learning implementation. One of the important aspects of Indonesian language learning is speaking skills, which serve as a means for students to express opinions, engage in discussions, and develop critical thinking abilities. In Grade V at MI Al Muawanah, challenges are still found, such as students’ low self-confidence, limited language mastery, and the dominance of high-achieving students during discussions. However, the group discussion method is considered relevant for improving speaking skills as it provides opportunities for students to actively interact and exchange ideas. This study aims to analyze teachers’ interpretations of the implementation of the group discussion method in developing elementary students’ speaking skills. The research employs a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation, while data analysis follows the Miles and Huberman model. The results reveal that teachers perceive the group discussion method as an effective means to enhance speaking skills, foster confidence, and strengthen social interactions among students. Despite existing challenges in its implementation, teachers believe that this method aligns with the objectives of Indonesian language learning and the current curriculum.